FROM CARE TO EDUCATION AN ORPHANAGE FOR DISABLED CHILDREN (Proceedings of International Conference on Special Education, 2017)
Children with disabilities, especially those with multiple disabilities, are often perceivedby comunnity as suffering from a disease. They are treated similar to treatments for those patients in the hospital with nurse assistance. Though in practice many of children with disabilities are self reliant.Several years ago the daily routines of children in care was very monotonous with minimal activity. From morning until evening the children spent most of their time in their bedroom, only occasionally were the children able to enjoy the outside environment. In 2013,we shifted from children with patient based treatment to more educational based programs. We are optimizing the services with currenthuman resources available in the center. We gradually meet the educational needs of the children. Staffs were recruited initially as caregivers before being retraining as educators. Additionally, it is very encouraging for the caregivers to be given the opportunity to become educators .As this has meant for their future career.To help us meet the target of the professional criteria of an educator we have enlisted the support of Perkins International. We are very pleased with the educational activities that have been promoted, children have begun to show huge amounts of progress - especially children who initially required full assistance in all developmental and functional activities. The help offered to children during activities is increasingly minimized as children gain learning experience and confidence. At present, during a few activities some children are no longer in need of any assistance. Our children have grown and now even take part in areas of work which previously were only done by adults. Now our children have become the growing, educationally aware focal point during each activity.